Nursing know-how. Interpreting ECG's. (Philadelphia, Pennsylvania : Lippincott Williams & Wilkins, 2009)
"In Nursing Know-How: Interpreting ECGs, you'll find: hundreds of ECG strips with complete analyse; alerts, to potential dangers associated with specific arrhythmias; dozens of practice strips to test your skill; and quick-scan ACLS algorithms from the American Heart Association."--Jacket
Cardiac anatomy and physiology -- ECG basics -- Rhythm strip interpretation -- Sinus node arrhythmias -- Atrial arrhythmias -- Junctional arrhythmias -- Ventricular arrhythmias -- Atrioventricular blocks -- Electrolyte imbalances and drugs -- Nonpharmacologic treatment -- Basic 12-lead electrocardiography -- Electrocardiogram analysis -- Disorders affecting 12-lead ECGS -- Rhythm strip exercises
Includes index.
Keywords: ELECTROCARDIOGRAPHY -- HANDBOOKS, MANUALS, ETC